HSD3B1 Genotype and Clinical Outcomes in Metastatic Castration-Sensitive Prostate Cancer - Hearn, Jason W. D. (JAMA Oncol, 2020)
IMPORTANCE: The adrenal-restrictive HSD3B1(1245A) allele limits extragonadal dihydrotestosterone synthesis, whereas the adrenal-permissive HSD3B1(1245C) allele augments extragonadal dihydrotestosterone synthesis. Retrospective studies have suggested an association between the adrenal-permissive allele, the frequency of which is highest in white men, and early development of castration-resistant prostate cancer (CRPC). OBJECTIVE: To examine the association between the adrenal-permissive HSD3B1(1245C) allele and early development of CRPC using prospective data. DESIGN, SETTING, AND PARTICIPANTS: The E3805 Chemohormonal Therapy vs Androgen Ablation Randomized Trial for Extensive Disease in Prostate Cancer (CHAARTED) was a large, multicenter, phase 3 trial of castration with or without docetaxel treatment in men with newly diagnosed metastatic prostate cancer. From July 28, 2006, through December 31, 2012, 790 patients underwent randomization, of whom 527 had available DNA samples. In this study, the HSD3B1 germline genotype was retrospectively determined in 475 white men treated in E3805 CHAARTED, and clinical outcomes were analyzed by genotype. Data analysis was performed from July 28, 2006, to October 17, 2018. INTERVENTIONS: Men were randomized to castration plus docetaxel, 75 mg/m(2), every 3 weeks for 6 cycles or castration alone. MAIN OUTCOMES AND MEASURES: Two-year freedom from CRPC and 5-year overall survival, with results stratified by disease volume. Patients were combined across study arms according to genotype to assess the overall outcome associated with genotype. Secondary analyses by treatment arm evaluated whether the docetaxel outcome varied with genotype. RESULTS: Of 475 white men with DNA samples, 270 patients (56.8%) inherited the adrenal-permissive genotype (≥1 HSD3B1[1245C] allele). Mean (SD) age was 63 (8.7) years. Freedom from CRPC at 2 years was diminished in men with low-volume disease with the adrenal-permissive vs adrenal-restrictive genotype: 51.0% (95% CI, 40.9%-61.2%) vs 70.5% (95% CI, 60.0%-80.9%) (P = .01). Overall survival at 5 years was also worse in men with low-volume disease with the adrenal-permissive genotype: 57.5% (95% CI, 47.4%-67.7%) vs 70.8% (95% CI, 60.3%-81.3%) (P = .03). Hazard ratios were 1.89 (95% CI, 1.13-3.14; P = .02) for CRPC and 1.74 (95% CI, 1.01-3.00; P = .045) for death. There was no association between genotype and outcomes in men with high-volume disease. There was no interaction between genotype and benefit from docetaxel. CONCLUSIONS AND RELEVANCE: Inheritance of the adrenal-permissive HSD3B1 genotype is associated with earlier castration resistance and shorter overall survival in men with low-volume metastatic prostate cancer and may help identify men more likely to benefit from escalated androgen receptor axis inhibition beyond gonadal testosterone suppression.